SBdP KIT: INOVASI MEDIA PEMBELAJARAN SENI RUPA PADA MATERI SENI DEKORASI MENGHIAS SISWA PENDIDIKAN DASAR - Ramadhani, Nadia Arsyida; Ysh., A. Y. Soegeng; Rofian (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
The 1945 Constitution and Law of the Republic of Indonesia Number 20 of 2003 which regulate the National Education System since August 17, 1945 became the legal basis for the curriculum developed by the Minister of National Education of the Republic of Indonesia. The Juridical Education Foundation is required by Article 31 of the 1945 Constitution to organize the state education system, prioritizing the advancement of science and technology, and 20% of the APBN and APBD budgets. This type of research is known as research and development (R&D), and modifies the early stages of development research using the ADDIE paradigm (Analysis, Design, Development, Implementation, and Evaluation). Teacher interviews, curriculum analysis, and small-scale SBdP KIT trials were used to collect data. This development research is a field test carried out in grade IV SD Negeri Tambak Boyo 02. The findings of this study show the great potential of SBdP KIT as a teaching tool that can deepen students' understanding of decoration. SBdP Kit media development can be well validated and is very feasible to use. The media trial was also very good and the response of students showed that this media was able to increase interest in learning and was able to explore student creativity.